A Fractional Variational Iteration Approach for Solving Time-Fractional Navier-Stokes Equations - M. Y Zayir; H Kamil Jassim (Mathematics and Computational Sciences, 2022)
The fractional variational iteration technique (FVIM), a dependable semi-analytic approach for solving multi-dimensional Navier-Stokes equations, is explained in this article. The accuracy, efficiency, and convergence of the provided approach are tested using a variety of demonstrative instances.